2018
DOI: 10.1002/hipo.22835
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the dopamine and noradrenergic cell loss that occurs in Parkinson's disease and the impact on hippocampal neurogenesis

Abstract: Key pathological features of Parkinson's Disease (PD) include the progressive degeneration of midbrain dopaminergic (DA) neurons and hindbrain noradrenergic (NA) neurons. The loss of DA neurons has been extensively studied and is the main cause of motor dysfunction. Importantly, however, there are a range of ‘non‐movement’ related features of PD including cognitive dysfunction, sleep disturbances and mood disorders. The origins for these non‐motor symptoms are less clear, but a possible substrate for cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 49 publications
0
18
0
2
Order By: Relevance
“…Such differential or even opposite effects of one humoral factor on the two major neurogenic niches of the adult mammalian brain have not been reported yet for other factors, though the role of the other catecholaminergic neurotransmitter, that is, dopamine, in the regulation of adult neurogenesis is also in part controversial. 56,61,64 Several lines of evidence suggest that reduced adult hippocampal neurogenesis is associated with depression and consistently the behavioral effects of noradrenergic antidepressants in animal models depend on the generation of new neurons within the hippocampus. 14,65 Our data might thus indicate a mechanistic link between body weight homeostasis and depression 66 via the opposite effects of NE released by LC neurons on PGN vs hippocampal neurogenesis, and provide an explanation for long-term body weight gain by centrally acting noradrenergic compounds such as various antidepressants.…”
Section: Discussionmentioning
confidence: 99%
“…Such differential or even opposite effects of one humoral factor on the two major neurogenic niches of the adult mammalian brain have not been reported yet for other factors, though the role of the other catecholaminergic neurotransmitter, that is, dopamine, in the regulation of adult neurogenesis is also in part controversial. 56,61,64 Several lines of evidence suggest that reduced adult hippocampal neurogenesis is associated with depression and consistently the behavioral effects of noradrenergic antidepressants in animal models depend on the generation of new neurons within the hippocampus. 14,65 Our data might thus indicate a mechanistic link between body weight homeostasis and depression 66 via the opposite effects of NE released by LC neurons on PGN vs hippocampal neurogenesis, and provide an explanation for long-term body weight gain by centrally acting noradrenergic compounds such as various antidepressants.…”
Section: Discussionmentioning
confidence: 99%
“…In PD, hippocampal non‐motor functions such as spatial learning and memory are impaired, and in several studies the impaired neurogenesis following DA depletion correlated with certain cognitive deficits observed in PD (Das et al, ; Klein et al, ; Lesemann et al, ; Sung, ). Other studies, however, showed no difference in proliferation or differentiation of newborn cells in the SGZ of the DG after DAergic lesions (Ermine et al, and refs therein). As different factors including age, sex, inflammation, the brain region examined, and the post‐injury interval considered, significantly affect the NSC response to injury (Figure ; and Figure S1) (Khan, Wakade, de Sevilla, Brann, ; L'Episcopo, , ; L'Episcopo, Tirolo, Serapide, et al, ; Tatar, Bessert, Tse, Skoff, , and following sections), it seems plausible that impairment of SVZ and SGZ neurogenesis in PD may well depend on both DAergic and non‐DAergic related mechanisms.…”
Section: Wnt/β‐catenin Signalling In Pdmentioning
confidence: 91%
“… 19 In contrast, a recent study demonstrated no change in NSC proliferation and newborn neuron formation in the hippocampus following the treatment of 6-OHDA in adult rats. 20 Neurogenic potential of NSCs in the brain is compromised during neurodegeneration as decreased proliferation of NSCs in DG and SVZ has also been reported in patients with PD, 13 suggesting that dopamine signalling regulates adult neurogenesis, but this notion requires further research to demonstrate the precise mechanism of action of dopamine.…”
Section: Introductionmentioning
confidence: 99%